The Effect of Iron (II) Chloride in Microalgae Cultivation for Bio-Oil Extraction - Tevan, R.; Saravanan, Jayakumar; Mohd Hasbi, Ab. Rahim; Gaanty Pragas, Maniam; Govindan, Natanamurugaraj (Research Malaysia Publications, 2017)
The world is facing a problem regarding the use of petroleum fuels that has led to a search for a suitable alternative fuel source. Researchers have come up with the idea of producing biofuel to overcome this problem. In this study, microalgae were explored as a high potential feedstock to produce biofuel. In order to produce a large quantity of biofuel with low cost at a short time, the manipulation of nutrients is a factor in microalgae cultivation. In this study, Iron (II) Chloride (FeCl2) was added to the nutrients to initiate a stressful condition during growth which contributes to the produce of lipid. Isolated microalgae species were identified as Scenedesmus sp. During mass cultivation, the microalgae cultures were scaled up to 2 L of culture. Three flasks of microalgae culture were labelled with S1, S2, and S3. Flask S1 acts as a control without the addition of FeCl2, while another two flasks acted as experimental flasks. Flask S2 was supplemented with 0.5 mg FeCl2 while Flask S3 was supplemented with 1.0 mg of FeCl2. With the addition of Iron (II) Chloride, microalgae entered a stationary phase at day 9 and day 10 as compared to the control flask which enters the stationary phase at day 7. This also affects the dry weight. Flask 3 produces 0.8658 g of microalgae powder compared to Flask 1 and 2 which produced 0.4649 g and 0.5357 g respectively. Lipid analysis was done by using GCMS and GC-FID. Flask 3 produced various types of fatty acids which can be used for biodiesel production compared to other cultivates. In Flask 1, docosanoic acid which is a saturated fatty acid was detected. While in Flask 2 (S2), with the addition of 0.5 mg of FeCl2, docosapentaenoic acid was produced. In the last flask which involved the addition of 1.0 mg of FeCl2, more fatty acid was detected. In GC-FID data, 6 types of fatty acids were detected. Linolein acid, linolenic acid, stearidonic acid, docosapentaenoic acid, docosahexaenoic acid and docosanoic acid were produced at different retention times. Most of the fatty acids produced are polyunsaturated fatty acid (PUFA). In transesterification, the fatty acid reacts with methanol and acid catalyst. The reaction produces fatty acid methyl ester. In Flask 1, the control flask, without the addition of FeCl2, no fatty acid methylesters (FAME) was produced. However, in Flask 2 and 3 which were added 0.5mg FeCl2 and 1.0 mg FeCl2, n-hexadecanoic acid methyl ester which is also known as palmitic acid was produced. Palmitic fatty acid can be used for biodiesel production.